NARP-related alterations in the excitatory and inhibitory circuitry of socially isolated mice: developmental insights and implications for autism spectrum disorder - Yamaguchi, Yasunari; Okamura, Kazuya; Yamamuro, Kazuhiko; Okumura, Kazuki; Komori, Takashi; Toritsuka, Michihiro; Takada, Ryohei; Nishihata, Yosuke; Ikawa, Daisuke; Yamauchi, Takahira; Makinodan, Manabu; Yoshino, Hiroki; et al. (Frontiers in Psychiatry, 2024)
Background: Social isolation during critical periods of development is associated with alterations in behavior and neuronal circuitry. This study aimed to investigate the immediate and developmental effects of social isolation on firing properties, neuronal activity-regulated pentraxin (NARP) and parvalbumin (PV) expression in the prefrontal cortex (PFC), social behavior in juvenile socially isolated mice, and the biological relevance of NARP expression in autism spectrum disorder (ASD). Methods: Mice were subjected to social isolation during postnatal days 21-35 (P21-P35) and were compared with group-housed control mice. Firing properties in the PFC pyramidal neurons were altered in P35 socially isolated mice, which might be associated with alterations in NARP and PV expression. Results: In adulthood, mice that underwent juvenile social isolation exhibited difficulty distinguishing between novel and familiar mice during a social memory task, while maintaining similar levels of social interaction as the control mice. Furthermore, a marked decrease in NARP expression in lymphoblastoid cell lines derived from adolescent humans with ASD as compared to typically developing (TD) humans was found. Conclusions: Our study highlights the role of electrophysiological properties, as well as NARP and PV expression in the PFC in mediating the developmental consequences of social isolation on behavior.